FLASH Radiotherapy: a Promising Direction in the Fight Against Cancer - А. V. Каrtashev; Т. N. Bochkareva; А. S. Anokhina (Вестник рентгенологии и радиологии, 2021)
At the present stage of scientific and technological progress, high-dose radiotherapy has become a common way to combat severe cancers. However, this treatment option is limited by normal tissues radiosensitivity. The developed technology of ultrashort pulse delivery of a dose of ionizing radiation to the zone of interest (FLASH radiotherapy) can achieve a high local control over tumor growth while sparing healthy tissues. This review summarizes the experimental findings supporting the possibility of transitioning to clinical studies of FLASH radiotherapy.